Hegemoni Antonio Gramsci: Sejarah dan Perkembangannya dalam Ranah Antropologi - Iklilah Muzayyanah Dini Fariyah (Antropologi Indonesia, 2011)
This writing is to parse the context of history from Antonio Gramsci’s thoughts regarding the concept of hegemony and positioning that approach in the realm of anthropological studies. The author wants to position Gramsci’s argument by outlining the opinions of the theory’s interpreters and explaining social and political context from the influences of Marxism and communism on Gramsci’s thinking. The fundamental concept of Gramschi’s thinking according to the auhor has influenced how post-1970s anthropology conceptualizes ideology, consent and hegemony as key issues that make the concept of culture become more operational in discussing matters of power. Keywords: Hegemony, Ideology, Historicity, Anthropology